دراسة طريقة رياضية لحساب الصمامات ذاتية التأثير للضواغط المكبسية ذات مراحل التبريد الصغيرة الحجم - اسبر, منى صافي; نصره, عواطف وحيد (Latakia University Journal -Engineering Sciences Series, 2013)
يهدف البحث إلى زيادة فعالية ووثوقية الصمامات وذلك بإيجاد طريقة رياضية تربط بارامترات الغاز مع الزمن. وتمّ على أساس هذا النموذج إنشاء طريقة لحساب عمل الصمامات والمبرداتمعاً، وذلك من خلال إنجاز المحاكاة العددية وتصميم برنامج لحساب هذه الصمامات. ومن ثم التوصل إلى الاستنتاجات والتوصيات التي تبيِّن تأثير حجم المبرد وانتقال الحرارةعلى عمل الضاغط بالإضافة إلى دراسة عمل الضاغط ضمن الأنظمة المتغيرة. The research aims to increase the effectiveness and reliability of valves by finding a mathematical way that links gas parameters with time. On the basis of this model, a method was created to calculate the way valves and chillers work together, through the achievement of numerical simulation and design of the program for counting these valves. Then, in addition to examining the function of the compressor, we consider conclusions and recommendations that show the effect of radiator size and heat transfer on the performance of the compressor,